Medical therapy versus myocardial revascularization in chronic coronary syndrome and stable angina - Deedwania, Prakash C; Carbajal, Enrique V (The American journal of medicine, 2011)
Coronary artery disease is a leading cause of death in the United States. Angina is encountered frequently in clinical practice. Effective management of patients with coronary artery disease and stable angina should consist of therapy aimed at symptom control and reduction of adverse clinical outcomes. Therapeutic options for angina include antianginal drugs: nitrates, beta-blockers, calcium channel blockers, ranolazine, and myocardial revascularization. Recent trials have shown that although revascularization is slightly better in controlling symptoms, optimal medical therapy that includes aggressive risk factor modification is equally effective in reducing the risk of future coronary events and death. On the basis of the available data, it seems appropriate to prescribe optimal medical therapy in most patients with coronary artery disease and stable angina, and reserve myocardial revascularization for selected patients with disabling symptoms despite optimal medical therapy.